Sustained, Multifaceted Improvements in Mental Well-Being Following Psychedelic Experiences in a Prospective Opportunity Sample - Mans, Keri; Kettner, Hannes; Erritzoe, David; Haijen, Eline C. H. M.; Kaelen, Mendel; Carhart-Harris, Robin L. (Frontiers in Psychiatry, 2021)
In the last fifteen years, psychedelic substances, such as LSD and psilocybin, have regained legitimacy in clinical research. In the general population as well as across various psychiatric populations, mental well-being has been found to significantly improve after a psychedelic experience. Mental well-being has large socioeconomic relevance, but it is a complex, multifaceted construct. In this naturalistic observational study, a comprehensive approach was taken to assessing well-being before and after a taking a psychedelic compound to induce a ‘psychedelic experience’. Fourteen measures of well-being related constructs were included in order to examine the breadth and specificity of change in well-being. This change was then analysed to examine clusters of measures changing together. Survey data was collected from volunteers that intended to take a psychedelic. Four key time points were analysed: one week before and two weeks, four weeks, and two years after the experience (N = 654, N = 315, N = 212, and N = 64 respectively). Change on the included measures was found to cluster into three factors which we labelled: 1) ‘Being well’, 2) ‘Staying well’, and 3) ‘Spirituality’. Repeated Measures Multivariate Analysis of Variance revealed all but the spirituality factor to be improved in the weeks following the psychedelic experience. Additional Mixed model analyses revealed selective increases in Being Well and Staying Well (but not Spirituality) that remained statistically significant up to two years post-experience, albeit with high attrition rates. Post-hoc examination suggested that attrition was not due to differential acute experiences or mental-health changes in those who dropped out versus those who did not. These findings suggest that psychedelics can have a broad, robust and sustained positive impact on mental well-being in those that have a prior intention to use a psychedelic compound. Public policy implications are discussed.